Prevalence and Predictors of Patent Ductus Arteriosus on Day 3 and Day 7 in Preterm Neonates: A Prospective Observational Study - Avinash Shukla; Amar Taksande (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Patent Ductus Arteriosus (PDA) refers to a persistent vascular connection between the pulmonary artery and the aorta. In a healthy newborn, this foetal vessel typically undergoes functional closure shortly after birth, followed by anatomical sealing. If the shunting is substantial, it can lead to significant haemodynamic instability. PDA is a common cardiovascular condition seen in neonates, particularly in preterm infants. As preterm birth is a significant contributor to neonatal mortality in India and other low-middle-income countries, understanding how PDA contributes to this burden is essential. By limiting the study to one specific rural hospital, the findings are highly relevant for similar settings and may serve as a baseline for future larger-scale or multicentric studies. Aim: To determine the prevalence of PDA on day 3 and day 7 of life in preterm neonates admitted to a rural neonatal intensive care unit and to assess its determinants, particularly gestational age and birth weight. Materials and Methods: The present prospective observational study was conducted in a rural tertiary care hospital, Neonatal Intensive Care Unit (NICU), Department of Paediatrics, at JNMC and AVBRH, Sawangi (Meghe), Wardha, Maharashtra, India from January 2023 to September 2024. A total of 100 preterm neonates with gestational age up to 34 weeks admitted to the neonatal intensive care unit were included. Echocardiographic assessment was performed on day 3 of life and repeated on day 7 in neonates with PDA. Determinants such as gestational age and birth weight were analysed. Data were analysed using statistical software, and Chi-square test was used to find association of gestational age and birth weight with PDA. A p-value less than 0.05 was considered statistically significant. Results: On day 3 of life, PDA was detected in 76% of preterm neonates. On repeat echocardiography on day 7, persistence of PDA was observed in 27% of neonates. Lower gestational age and lower birth weight were significantly associated with persistence of PDA, indicating prematurity as a major determinant. Conclusion: The present study highlights PDA as a prevalent condition contributing significantly to early complications and death. The most affected infants were those born before 30 weeks of gestation and those with extremely low birth weights.